Electrochemically reduced single-layer MoS2 nanosheets : characterization, properties, and sensing applications - Wu, Shixin (2013)
The electrochemical study of single-layer, 2D MoS2 nanosheets reveals a reduction peak in the cyclic voltammetry in NaCl aqueous solution. The electrochemically reduced MoS2 (rMoS2) shows good conductivity and fast electron transfer rate in the [Fe(CN)6]3-/4− and [Ru(NH3)6]2+/3+ redox systems. The obtained rMoS2 can be used for glucose detection. In addition, it can selectively detect dopamine in the presence of ascorbic acid and uric acid. This novel material, rMoS2, is believed to be a good electrode material for electrochemical sensing applications.